High-temperature-resistant modified nano silicon dioxide hyperbranched oil well cement fluid loss agent and preparation method thereof
By using high-temperature modified nano-silica superbranched oil well cement loss-reducing agent, the problem of poor water loss-reducing agent in the prior art oil well cement loss-reducing agent in high-temperature environment is solved, and excellent water loss-reducing performance and stable cementing effect under high temperature conditions are achieved.
Patent Information
- Application Number
- CN202311202831.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing oil well cement loss-depleting agent has poor performance in high-temperature environments, resulting in poor filtration loss of cement slurry, affecting cement quality and safety.
The anti-high-temperature modified nanosilica superbranched oil well cement water loss reduction agent is used. This agent is prepared by specific synthesis methods to form an efficient water loss reduction agent.
The water loss reducing agent exhibits excellent water loss performance under high temperature conditions from 120°C to 180°C, effectively controls the filtration loss rate of the cement slurry, maintains the water-solid ratio unchanged, and improves cementing quality and safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil well cement fluid loss reducer, in particular to a high temperature resistant modified nano silicon dioxide hyperbranched oil well cement fluid loss reducer and a preparation method thereof. Background Art
[0002] As oil and gas exploration and development gradually develops towards deep wells and ultra-deep wells, the temperature in the wells increases and the pressure increases. Under high temperature conditions, the cement slurry used for cementing will lose a lot of water. The filtration loss of cement slurry will cause the fluidity of cement slurry to deteriorate, and the filtrate entering the bottom will cause damage to the formation. Oil well cement fluid loss reducer is an important cement admixture commonly used in cementing. By controlling the penetration of the liquid phase in the cement slurry into the formation, it plays a key role in improving the quality of cementing, ensuring the safety of cementing operations, and protecting the oil and gas layers from pollution.
[0003] At present, there are many types of commonly used oil well cement fluid loss reducers with different performance differences. AMPS copolymers have become a hot spot for polymer synthesis at home and abroad due to their excellent heat and salt resistance. AMPS polymers have designable molecular structures, excellent heat and salt resistance, and strong water loss reduction capabilities, but they are also difficult to solve the water loss problem of cement slurry under high temperature environments. There are few cementing admixture products suitable for 180°C in China, and foreign products are expensive. Moreover, when the temperature is between 120°C and 180°C, the performance of domestic cementing admixture products is unstable and the cementing quality is difficult to control. Summary of the invention
[0004] The present invention provides a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer and a preparation method thereof, which overcomes the above-mentioned deficiencies of the prior art and can effectively solve the problem that the existing cementing cement fluid loss reducer has poor fluid loss performance in a high temperature environment.
[0005] One of the technical solutions of the present invention is achieved through the following measures: a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer, the raw materials of which include 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10: (3.5 to 4.0): (3.5 to 4.0): 2: 1.
[0006] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions: The high temperature resistant modified nano-silicon dioxide hyperbranched oil well cement fluid loss reducing agent is obtained according to the following method: S1, dissolving the required amount of 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid in water to obtain a mixed solution, adjusting the pH of the mixed solution, and then adding the required amount of acrylamide, N-vinyl pyrrolidone and modified nano-silica in sequence, stirring until completely dissolved, to obtain a mixed monomer solution; S2, placing the mixed monomer solution in a nitrogen atmosphere, adding a required amount of initiator solution to the mixed monomer solution under stirring, and heating for reaction to obtain an intermediate product; S3, washing the intermediate product with anhydrous ethanol, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0007] In the above step S1, the total mass concentration of monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution is 15% to 25%, and the pH value of the mixed solution is adjusted to 7 to 8 using a sodium hydroxide solution with a mass concentration of 30%.
[0008] In the above step S2, the amount of the initiator solution added is 0.15% to 0.25% of the total mass of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution, the initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 3% to 5%.
[0009] In the above step S2, nitrogen is introduced into the mixed monomer solution for 15 to 30 minutes to place it in a nitrogen atmosphere, the stirring speed is 200 to 400 r / min, the reaction temperature is 50° C. to 60° C., and the reaction time is 5 to 6 hours.
[0010] In the above step S3, the amount of anhydrous ethanol used is 3 to 5 times the volume of the intermediate product.
[0011] The modified nano silicon dioxide is obtained by the following method: The first step is to add 4 to 6 parts by weight of nano-silicon dioxide to 110 to 130 parts of toluene, and obtain a toluene solution of nano-silicon dioxide after ultrasonic dispersion; The second step is to drop 630 to 640 parts of 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) into the toluene solution of nano-silica under stirring conditions for reflux reaction to obtain an intermediate product; In the third step, the intermediate product is subjected to rotary evaporation, washing, suction filtration and drying to obtain modified nano-silica.
[0012] In the first step, the ultrasonic dispersion time is 30 min to 50 min.
[0013] In the second step, during the reflux reaction, the temperature is 75° C. to 85° C., and the time is 10 h to 14 h.
[0014] In the third step, the drying temperature is 65° C. to 75° C., and the drying time is 22 h to 24 h.
[0015] The second technical solution of the present invention is achieved by the following measures: A method for preparing a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer is carried out according to the following method: S1, dissolving the required amount of 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid in water, adjusting the pH of the solution, and then sequentially adding the required amount of acrylamide, N-vinyl pyrrolidone and modified nano-silica, stirring until completely dissolved, to obtain a mixed monomer solution; S2, placing the mixed monomer solution in a nitrogen atmosphere, adding a required amount of initiator solution to the mixed monomer solution under stirring, and heating for reaction to obtain an intermediate product; S3, washing the intermediate product with anhydrous ethanol, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0016] The high temperature resistant modified nano silica hyperbranched oil well cement fluid loss reducer of the present invention has excellent fluid loss reducing performance. The cement slurry to which the high temperature resistant modified nano silica hyperbranched oil well cement fluid loss reducer of the present invention is added can effectively improve its fluid loss performance under high temperature environment and can effectively control the filtration rate of the cement slurry to maintain its water-to-solid ratio unchanged. DETAILED DESCRIPTION
[0017] The present invention is not limited by the following embodiments, and the specific implementation method can be determined according to the technical scheme of the present invention and the actual situation. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all chemical reagents and chemicals known and used in the prior art; unless otherwise specified, the percentages in the present invention are all mass percentages; unless otherwise specified, the solutions in the present invention are all aqueous solutions with water as the solvent, for example, hydrochloric acid solution is a hydrochloric acid aqueous solution; the normal temperature and room temperature in the present invention generally refer to a temperature of 15°C to 25°C, and are generally defined as 25°C.
[0018] The present invention will be further described below in conjunction with embodiments: Example 1: The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer comprises raw materials of 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10:(3.5 to 4.0):(3.5 to 4.0):2:1.
[0019] Example 2: As an optimization of the above example, a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer is obtained by the following method: S1, dissolving the required amount of 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid in water, adjusting the pH of the solution, and then sequentially adding the required amount of acrylamide, N-vinyl pyrrolidone and modified nano-silica, stirring until completely dissolved, to obtain a mixed monomer solution; S2, placing the mixed monomer solution in a nitrogen atmosphere, adding a required amount of initiator solution to the mixed monomer solution under stirring, and heating for reaction to obtain an intermediate product; S3, washing the intermediate product with anhydrous ethanol, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0020] Example 3: As an optimization of the above example, in step S1, the total mass concentration of monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution is 15% to 25%, and the pH value of the mixed solution is adjusted to 7 to 8 using a sodium hydroxide solution with a mass concentration of 30%.
[0021] Example 4: As an optimization of the above example, in step S2, the amount of initiator solution added is 0.15% to 0.25% of the total mass of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution, the initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 3% to 5%.
[0022] Example 5: As an optimization of the above example, in step S2, nitrogen is introduced into the mixed monomer solution for 15 to 30 minutes to place it in a nitrogen atmosphere, the stirring speed is 200 to 400 r / min, the reaction temperature is 50 to 60°C, and the reaction time is 5 to 6 hours.
[0023] Example 6: As an optimization of the above example, in step S3, the amount of anhydrous ethanol used is 3 to 5 times the volume of the intermediate product.
[0024] Example 7: As an optimization of the above example, modified nano-silicon dioxide is obtained by the following method: The first step is to add 4 to 6 parts by weight of nano-silicon dioxide to 110 to 130 parts of toluene, and obtain a toluene solution of nano-silicon dioxide after ultrasonic dispersion; The second step is to drop 630 to 640 parts of 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) into the toluene solution of nano-silica under stirring conditions for reflux reaction to obtain an intermediate product; In the third step, the intermediate product is subjected to rotary evaporation, washing, suction filtration and drying to obtain modified nano-silica.
[0025] Example 8: As an optimization of the above example, in the first step, the ultrasonic dispersion time is 30 min to 50 min.
[0026] Example 9: As an optimization of the above example, in the second step, during the reflux reaction, the temperature is 75°C to 85°C, and the time is 10h to 14h.
[0027] Example 10: As an optimization of the above example, in the third step, the drying temperature is 65°C to 75°C, and the drying time is 22h to 24h.
[0028] The high temperature resistant modified nano silica hyperbranched oil well cement fluid loss reducer prepared by the invention is a tetrapolymer type fluid loss reducer with nano silica particles added thereto. The raw material 2-acrylamide-2-methylpropane sulfonic acid (AMPS) has the characteristics of excellent heat resistance and salt resistance and strong water loss reduction ability. The raw material nano silica has high surface energy, high strength, high stability and excellent thermal stability. In the process of synthesizing the polymer, the nano silica particles are introduced to improve the heat resistance of the high temperature resistant modified nano silica hyperbranched oil well cement fluid loss reducer, thereby solving the water loss problem of cement slurry under high temperature environment.
[0029] Embodiment 11: The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer comprises raw materials including 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10:3.5:3.5:2:1, and is obtained by the following method: S1, dissolving 10 g of 2-acrylamide-2-methylpropanesulfonic acid and 3.5 g of acrylic acid in water to obtain a mixed solution, adjusting the pH value of the mixed solution to 7 with a sodium hydroxide solution having a mass concentration of 30%, and then sequentially adding 3.5 g of acrylamide, 2 g of N-vinyl pyrrolidone and 1 g of modified nano-silica, stirring until completely dissolved to obtain a mixed monomer solution; wherein the total mass concentration of monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution is 15%; S2, placing the mixed monomer solution in a reaction kettle, introducing nitrogen into the kettle for 15 minutes, adding the required amount of initiator solution to the mixed monomer solution at a stirring speed of 200 r / min, heating to 50°C for reaction for 5 hours, and obtaining an intermediate product; wherein, the amount of the initiator solution added is 0.15% of the total mass of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution, the initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 3%; S3, washing the intermediate product with anhydrous ethanol in an amount three times the volume of the intermediate product, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0030] Wherein, the modified nano silicon dioxide is obtained by the following method: In the first step, 4 g of nano-silicon dioxide was added to 110 g of toluene, and then ultrasonically dispersed for 30 min to obtain a toluene solution of nano-silicon dioxide. The second step is to add 630 g of 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) dropwise to the toluene solution of nano-silica under stirring, and reflux at 75° C. for 10 hours to obtain an intermediate product; In the third step, the intermediate product is subjected to multiple rotary evaporation, washing, and suction filtration with anhydrous ethanol to remove unreacted monomers, and then dried at 65° C. for 22 hours to obtain modified nano-silica.
[0031] Embodiment 12: The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer comprises raw materials including 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10:4:4:2:1, and is obtained by the following method: S1, dissolving 10 g of 2-acrylamide-2-methylpropanesulfonic acid and 4 g of acrylic acid in water to obtain a mixed solution, adjusting the pH value of the mixed solution to 8 with a sodium hydroxide solution having a mass concentration of 30%, and then adding 4 g of acrylamide, 2 g of N-vinyl pyrrolidone and 1 g of modified nano-silica in sequence, stirring until completely dissolved, to obtain a mixed monomer solution; wherein the total mass concentration of monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution is 25%; S2, placing the mixed monomer solution in a reactor, introducing nitrogen into the reactor for 30 minutes, adding a required amount of initiator solution to the mixed monomer solution at a stirring speed of 400 r / min, heating to 60°C for reaction for 6 hours, and obtaining an intermediate product; wherein, the amount of the initiator solution added is 0.25% of the total mass of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution, the initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 5%; S3, washing the intermediate product with anhydrous ethanol in an amount 5 times the volume of the intermediate product, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0032] Wherein, the modified nano silicon dioxide is obtained by the following method: In the first step, 6 g of nano-silicon dioxide was added to 130 g of toluene, and then ultrasonically dispersed for 50 min to obtain a toluene solution of nano-silicon dioxide. The second step is to add 640 g of 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) dropwise to the toluene solution of nano-silica under stirring, and reflux at 85° C. for 14 hours to obtain an intermediate product; In the third step, the intermediate product is subjected to multiple rotary evaporation, washing, and suction filtration with anhydrous ethanol to remove unreacted monomers, and then dried at 75° C. for 24 hours to obtain modified nano-silica.
[0033] Embodiment 13: The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer comprises raw materials including 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10:3.8:3.8:2:1, and is obtained by the following method: S1, dissolving 10 g of 2-acrylamide-2-methylpropanesulfonic acid and 3.8 g of acrylic acid in water to obtain a mixed solution, adjusting the pH value of the mixed solution to 7.5 with a sodium hydroxide solution having a mass concentration of 30%, and then sequentially adding 3.8 g of acrylamide, 2 g of N-vinyl pyrrolidone and 1 g of modified nano-silica, stirring until completely dissolved to obtain a mixed monomer solution; wherein the total mass concentration of monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution is 20%; S2, placing the mixed monomer solution in a reactor, introducing nitrogen into the reactor for 25 minutes, adding a required amount of initiator solution to the mixed monomer solution at a stirring speed of 300 r / min, heating to 55°C for reaction for 5.5 hours, and obtaining an intermediate product; wherein, the amount of the initiator solution added is 0.20% of the total mass of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution, the initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 4%; S3, washing the intermediate product with anhydrous ethanol in an amount 4 times the volume of the intermediate product, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0034] Wherein, the modified nano silicon dioxide is obtained by the following method: In the first step, 5 g of nano-silicon dioxide was added to 120 g of toluene, and then ultrasonically dispersed for 40 min to obtain a toluene solution of nano-silicon dioxide. The second step is to add 635 g of 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) dropwise to the toluene solution of nano-silica under stirring, and reflux at 80° C. for 12 hours to obtain an intermediate product; In the third step, the intermediate product is subjected to multiple rotary evaporation, washing, and suction filtration with anhydrous ethanol to remove unreacted monomers, and then dried at 70° C. for 23 h to obtain modified nano-silica.
[0035] Compared with the prior art, the present invention has the following beneficial effects: At present, there are few cementing admixture products suitable for 180°C in China, and the cost of foreign cementing admixture products is high. In the range of 120°C to 180°C, the performance of domestic cementing admixture products is unstable, and the cementing quality is difficult to control. The high-temperature resistant modified nano-silicon dioxide hyperbranched oil well cement fluid loss reducer of the present invention can effectively resist 180°C high temperature, has stable performance, and has good cementing effect. The high-temperature resistant modified nano-silicon dioxide hyperbranched oil well cement fluid loss reducer prepared by the present invention is added to the oil field cementing cement slurry at a mass ratio of 2% to 5%. At a temperature of 120°C to 180°C and a pressure of 6.9MPa, its water loss is less than 50mL, indicating that the high-temperature resistant modified nano-silicon dioxide hyperbranched oil well cement fluid loss reducer of the present invention has good water loss reduction performance under high temperature conditions.
[0036] Embodiment 14: The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer comprises raw materials including 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10:3.5:4:2:1, and is obtained by the following method: S1, dissolving 10 g of 2-acrylamide-2-methylpropanesulfonic acid and 3.5 g of acrylic acid in water to obtain a mixed solution, adjusting the pH value of the mixed solution to 7 with a sodium hydroxide solution having a mass concentration of 30%, and then sequentially adding 4 g of acrylamide, 2 g of N-vinyl pyrrolidone and 1 g of modified nano-silica, stirring until completely dissolved to obtain a mixed monomer solution; wherein the total mass concentration of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution is 15% to 25%; S2, placing the mixed monomer solution in a reaction kettle, introducing nitrogen into the kettle for 15 minutes, adding the required amount of initiator solution to the mixed monomer solution at a stirring speed of 200 r / min, heating to 50°C for reaction for 5 hours, and obtaining an intermediate product; wherein, the amount of the initiator solution added is 0.15% of the total mass of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution, the initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 3%; S3, washing the intermediate product with anhydrous ethanol in an amount three times the volume of the intermediate product, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0037] Wherein, the modified nano silicon dioxide is obtained by the following method: In the first step, 4 g of nano-silicon dioxide was added to 110 g of toluene, and then ultrasonically dispersed for 30 min to obtain a toluene solution of nano-silicon dioxide. The second step is to add 630 g of 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) dropwise to the toluene solution of nano-silica under stirring, and reflux at 75° C. for 10 hours to obtain an intermediate product; In the third step, the intermediate product is subjected to multiple rotary evaporation, washing, and suction filtration with anhydrous ethanol to remove unreacted monomers, and then dried at 65° C. for 22 hours to obtain modified nano-silica.
[0038] Embodiment 15: The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer comprises raw materials including 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10:3.5:4:2:1, and is obtained by the following method: S1, dissolving 10 g of 2-acrylamide-2-methylpropanesulfonic acid and 3.5 g of acrylic acid in water to obtain a mixed solution, adjusting the pH value of the mixed solution to 8 with a sodium hydroxide solution having a mass concentration of 30%, and then sequentially adding 4 g of acrylamide, 2 g of N-vinyl pyrrolidone and 1 g of modified nano-silica, stirring until completely dissolved to obtain a mixed monomer solution; wherein the total mass concentration of monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution is 25%; S2, placing the mixed monomer solution in a reactor, introducing nitrogen into the reactor for 30 minutes, adding a required amount of initiator solution to the mixed monomer solution at a stirring speed of 400 r / min, heating to 60°C for reaction for 6 hours, and obtaining an intermediate product; wherein, the amount of the initiator solution added is 0.25% of the total mass of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution, the initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 5%; S3, washing the intermediate product with anhydrous ethanol in an amount 5 times the volume of the intermediate product, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0039] Wherein, the modified nano silicon dioxide is obtained by the following method: In the first step, 6 g of nano-silicon dioxide was added to 130 g of toluene, and then ultrasonically dispersed for 50 min to obtain a toluene solution of nano-silicon dioxide. The second step is to add 640 g of 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) dropwise to the toluene solution of nano-silica under stirring, and reflux at 85° C. for 14 hours to obtain an intermediate product; In the third step, the intermediate product is subjected to multiple rotary evaporation, washing, and suction filtration with anhydrous ethanol to remove unreacted monomers, and then dried at 75° C. for 24 hours to obtain modified nano-silica.
[0040] Embodiment 16: The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer comprises raw materials including 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10:3.5:4:2:1, and is obtained by the following method: S1, dissolving 10 g of 2-acrylamide-2-methylpropanesulfonic acid and 3.5 g of acrylic acid in water to obtain a mixed solution, adjusting the pH value of the mixed solution to 7.5 with a sodium hydroxide solution having a mass concentration of 30%, and then sequentially adding 4 g of acrylamide, 2 g of N-vinyl pyrrolidone and 1 g of modified nano-silica, stirring until completely dissolved to obtain a mixed monomer solution; wherein the total mass concentration of monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution is 20%; S2, placing the mixed monomer solution in a reactor, introducing nitrogen into the reactor for 25 minutes, adding a required amount of initiator solution to the mixed monomer solution at a stirring speed of 300 r / min, heating to 55°C for reaction for 5.5 hours, and obtaining an intermediate product; wherein, the amount of the initiator solution added is 0.20% of the total mass of the monomers (2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica) in the mixed monomer solution, the initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 4%; S3, washing the intermediate product with anhydrous ethanol in an amount 4 times the volume of the intermediate product, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
[0041] Wherein, the modified nano silicon dioxide is obtained by the following method: The first step is to add 5g of nano-silicon dioxide to 120g of toluene, and then ultrasonically disperse the nano-silicon dioxide for 30 to 50 minutes to obtain a toluene solution of the nano-silicon dioxide. The second step is to add 634 g of 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) dropwise to the toluene solution of nano-silica under stirring, and reflux at 80° C. for 12 hours to obtain an intermediate product; In the third step, the intermediate product is subjected to multiple rotary evaporation, washing, and suction filtration with anhydrous ethanol to remove unreacted monomers, and then dried at 70° C. for 23 h to obtain modified nano-silica.
[0042] Comparative Example 1: The difference from Example 16 is that no modified nano-silicon dioxide is added to the raw materials, and the remaining steps are the same as those of Example 16 to obtain an oil well cement fluid loss reducer.
[0043] Example 17: The high temperature resistant modified nano silica hyperbranched oil well cement fluid loss reducer prepared in Examples 14 to 16 of the present invention is added to the oil field cementing cement slurry respectively. At the same time, Comparative Example 1 is used as a control. The formula of the oil field cementing cement slurry is: G grade cement + 35% silica powder + high temperature resistant modified nano silica hyperbranched oil well cement fluid loss reducer + 1% to 2% retarder + 0.1% defoamer + 0.1% to 0.3% dispersant + water.
[0044] Based on the formula of oilfield cementing slurry, 2.5%, 4.0% and 5.0% of the high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer prepared in Example 14 of the present invention were added to the oil well cementing slurry, respectively, to obtain cement slurry A with different addition amounts; 2.5%, 4.0% and 5.0% of the high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer prepared in Example 15 of the present invention were added to the oil well cementing slurry, respectively, to obtain cement slurry B with different addition amounts; 2.5%, 4.0% and 5.0% of the high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer prepared in Example 16 of the present invention were added to the oil well cementing slurry, respectively, to obtain cement slurry C with different addition amounts; at the same time, 2.5%, 4.0% and 5.0% of the oil well cement fluid loss reducer prepared in Comparative Example 1 of the present invention were added to the oil well cementing slurry, respectively, to obtain cement slurry D with different addition amounts.
[0045] The water loss test of cement slurry A, cement slurry B, cement slurry C and cement slurry D with an addition amount of 2.5% was carried out at a temperature of 6.9 MPa and 120°C. The water loss test of cement slurry A, cement slurry B, cement slurry C and cement slurry D with an addition amount of 4.0% of the fluid loss agent was carried out at a temperature of 6.9 MPa and 150°C. The water loss test of cement slurry A, cement slurry B, cement slurry C and cement slurry D with an addition amount of 5.0% of the fluid loss agent was carried out at a temperature of 6.9 MPa and 180°C.
[0046] The test results of water loss of each cement slurry are shown in Table 1. It can be seen from Table 1 that the high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer of the present invention has good rheological control over cement. The cement slurry obtained by using the high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer of the present invention as a raw material can be controlled within 50 mL of API water loss under the conditions of temperature 180°C and pressure 6.9 MPa.
[0047] In summary, the high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer of the present invention has excellent water loss reduction performance, and the cement slurry added with the high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer can effectively improve its water loss performance under high temperature environment, and can effectively control the filtration rate of the cement slurry to maintain its water-to-solid ratio unchanged.
[0048] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.
Claims
1. A high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer, characterized in that The raw materials include 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinyl pyrrolidone and modified nano-silica in a mass ratio of 10:3.5 to 4.0:3.5 to 4.0:2:
1.
2. The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to claim 1, characterized in that Obtained as follows: S1, dissolving the required amount of 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid in water to obtain a mixed solution, adjusting the pH of the mixed solution, and then adding the required amount of acrylamide, N-vinyl pyrrolidone and modified nano-silica in sequence, stirring until completely dissolved, to obtain a mixed monomer solution; S2, placing the mixed monomer solution in a nitrogen atmosphere, adding a required amount of initiator solution to the mixed monomer solution under stirring, and heating for reaction to obtain an intermediate product; S3, washing the intermediate product with anhydrous ethanol, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
3. The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to claim 1 or 2, characterized in that In step S1, the total mass concentration of monomers in the mixed monomer solution is 15% to 25%, and the pH value of the mixed solution is adjusted to 7 to 8 using a sodium hydroxide solution with a mass concentration of 30%.
4. The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to claim 1, 2 or 3, characterized in that In step S2, the amount of the initiator solution added is 0.15% to 0.25% of the total mass of the monomers in the mixed monomer solution. The initiator is a mixture of ammonium persulfate and sodium bisulfite in a mass ratio of 1:1, and the mass concentration of the initiator in the initiator solution is 3% to 5%.
5. The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to any one of claims 1 to 4, characterized in that In step S2, nitrogen is introduced into the mixed monomer solution for 15 to 30 minutes to place it in a nitrogen atmosphere, the stirring speed is 200 to 400 r / min, the reaction temperature is 50° C. to 60° C., and the reaction time is 5 to 6 hours.
6. The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to any one of claims 1 to 5, characterized in that In step S3, the amount of anhydrous ethanol used is 3 to 5 times the volume of the intermediate product.
7. The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to any one of claims 1 to 6, characterized in that Modified nano-silicon dioxide is obtained by the following method: The first step is to add 4 to 6 parts by weight of nano-silicon dioxide to 110 to 130 parts of toluene, and obtain a toluene solution of nano-silicon dioxide after ultrasonic dispersion; The second step is to drop 630 to 640 parts of 3-aminopropyltrimethoxysilane into the toluene solution of nano-silicon dioxide under stirring, and then reflux the solution to obtain an intermediate product. In the third step, the intermediate product is subjected to rotary evaporation, washing, suction filtration and drying to obtain modified nano-silica.
8. The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to claim 7, characterized in that In the first step, the ultrasonic dispersion time is 30 min to 50 min; or / and, in the second step, during the reflux reaction, the temperature is 75° C. to 85° C. and the time is 10 h to 14 h.
9. The high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to claim 7 or 8, characterized in that In the third step, the drying temperature is 65° C. to 75° C., and the drying time is 22 h to 24 h.
10. A method for preparing a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer according to any one of claims 1, 3 to 9, characterized in that Proceed as follows: S1, dissolving the required amount of 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid in water to obtain a mixed solution, adjusting the pH of the mixed solution, and then adding the required amount of acrylamide, N-vinyl pyrrolidone and modified nano-silica in sequence, stirring until completely dissolved, to obtain a mixed monomer solution; S2, placing the mixed monomer solution in a nitrogen atmosphere, adding a required amount of initiator solution to the mixed monomer solution under stirring, and heating for reaction to obtain an intermediate product; S3, washing the intermediate product with anhydrous ethanol, filtering, drying and grinding to obtain a high temperature resistant modified nano-silica hyperbranched oil well cement fluid loss reducer.
Citation Information
Patent Citations
Multi-element co-polymerization oil well cement fluid loss additive and preparation method thereof
CN101397491A
Preparation method of polymer fluid loss agent for sulphoaluminate cement
CN106632917A
Inorganic-organic polymer oil well cement filtrate loss reduction additive, and preparation method and application thereof
CN109503782A